Patterns and outcomes of posterior fossa extradural hematoma-six years study in emergency hospitals of Erbil city - Gulshan Talat Muhammed; Sameer Hassan Aboud (Advanced Medical Journal)
Background and objectives: Posterior fossa extradural hematoma is rare , however, in clinical practice it may represent a top emergency. The aim of study was to find the proportion of posterior fossa extradural hematoma to other extradural hematomas, its age incidence, main causes and factors that affect surgery and outcomes.